Quantum Dots as Theranostic Agents: Recent Advancements, Surface Modifications, and Future Applications - Phafat, Bhushan; Bhattacharya, Sankha (Mini Reviews in Medicinal Chemistry, 2023)
The use of quantum technology to deliver drugs has the potential to increase the efficacy of many rare disease treatments. Semiconductor nanoparticles are a new type of treatment for life-threatening disorders. The term
Keywords: biosensors